Role of quaternary N in N-doped graphene–Fe2O3 nanocomposites as efficient photocatalysts for CO2 reduction and acetaldehyde degradation. Issue 103 (7th October 2015) - Wang, Hongjian; Raziq, Fazal; Qu, Yang; Qin, Chuanli; Wang, Jinshuang; Jing, Liqiang
Abstract : The quaternary N in N-doped graphene–Fe2 O3 nanocomposites contributes to the obviously-improved photoactivities for CO2 reduction and for acetaldehyde degradation. Abstract : The quaternary N in N-doped graphene–Fe2 O3 nanocomposites could be very favorable for the transfer and transportation of photogenerated charges and for the adsorption of CO2 and O2 so as to greatly enhance the charge separation, leading to the obviously-improved photoactivities for CO2 reduction to selectively evolve CO and for acetaldehyde degradation.